An Au(iii)–amino alcohol complex for degradation of organophosphorus pesticides. Issue 129 (18th December 2015) - Ferri, D.; Barba-Bon, A.; Costero, A. M.; Gaviña, P.; Parra, M.; Gil, S.
Abstract : A gold(iii )–amino alcohol complex induces the P–S bond cleavage in organophosphorous pesticides giving rise to less toxic compounds. Abstract : An Au(iii )–amino alcohol complex has been used to cleave organophosphorous pesticides of the dithiophosphate family. P–S bond breaking was readily demonstrated by 1 H NMR, 31 P NMR and MS. Thiol fragment release was also demonstrated using 2, 4-dinitrobenzenesulfonyl fluorescein ethyl ester as a fluorescent sensor.